ESTIMATION OF GENETIC PARAMETERS AND BREEDING VALUES FOR DAIRY CATTLE USING TEST-DAY MILK YIELD RECORDS - A. Kaygisiz (Journal of Animal and Plant Sciences, 2013)
The aim of this study was to estimate genetic parameters and breeding values for 305-d and test-days (TD) milk yields, and to compare the obtained results. For this aim, the data were collected during the years of 1989 and 2007 for 11200 lactation records of Holstein cattle reared at Ceylanpinar State Farm in the Southern East Region of Türkiye. The 305-d milk yield of each animal was calculated using the Test Interval Method (TIM). Additive genetic, residual and permanent environmental variances, heritabilities and breeding values for 305-d and TD milk yields were estimated by using the REML method on the basis of animal models. Heritability of test day milk yield (0.15) was lower than the heritability of 305-d milk yield (0.20). Pearson, Spearman and Kendall correlation coefficients between breeding values for test day and 305-d milk yield were estimated as: 0.90, 0.90 and 0.74 (P<0.01) for bulls and 0.78, 0.92 and 0.76 (P<0.01) for cows, respectively. Present results reflected that use of test day milk yields could be suggested to estimate 305-d milk yield for the genetic evaluation of dairy cows. Furthermore, use of TD milk yield for genetic evaluations permits researchers to gain more advantages.
Keywords: Holstein Cattle; 305-d Milk Yield; Test Day Yield; Genetic Parameters; Breeding Value